DESIGN AND SIMULATION OF AXIAL DUCTED FAN OF APPROXIMATELY 3,5 M3 NIKOLAI RAMOS /S FLOW RATE - RAMOS ADELBERT SIRAIT (NIM : 13105136); Pembimbing : Dr.Ir. Priyono Sutikno, NIKOLAI
Ducted axial fan is one of turbo machinery which converts mechanics energy into fluid energy. The duty of fan is to provide an increasing volume at high pressure. This duty then applied in many kinds of application in industry nowadays. In this final project, we will design a ducted axial fan, and the outlet flow rate of the researched fan will be used as a source of velocity and pressure for wind turbine which is being developed in Laboratory of Fluid Mechanics. First step of designing process is to determine some initial parameters, such as fluid inlet velocity, fan diameter, boss diameter, shaft rotational velocity, and the system efficiency. Then we need to calculate the fan parameter based on the initial one. The fan parameter includes tangential velocity, impeller relative speed, Cu, Ca, W∞ , β, β∞, chord length, lift and drag coefficient, torque, power and the fan efficiency. The required performance of the ducted axial fan is 3,5 m3/s outlet flow rate with 1 m diameter of longitudinal section. In order to achieve that performance we need to put all the parameter values into calculation and iteration. The result of the calculation is that we need to get a 458 Watt power and 85 % fan system efficiency. All those parameter then applied in a three dimension sketch using Autodesk Inventor 2010 software. The three dimension sketch of fan is then simulated using CFD Gambit 2.2.30 and FLUENT 6.3.26 software. And the efficiency result is quite close, approximately 71,09%.